2020
DOI: 10.1038/s41467-019-14268-x
|View full text |Cite
|
Sign up to set email alerts
|

Attosecond optoelectronic field measurement in solids

Abstract: The sub-cycle interaction of light and matter is one of the key frontiers of inquiry made accessible by attosecond science. Here, we show that when light excites a pair of charge carriers inside of a solid, the transition probability is strongly localized to instants slightly after the extrema of the electric field. The extreme temporal localization is utilized in a simple electronic circuit to record the waveforms of infrared to ultraviolet light fields. This form of petahertz-bandwidth field metrology gives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 43 publications
0
84
0
Order By: Relevance
“…n recent years, the combination of nano-optical structures with intense, few-cycle laser sources has led to a new class of solid-state petahertz electronic devices with promising applications in time-domain metrology as well as information processing [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . These petahertz devices rely on the attosecond-level temporal response of optical-field-driven photocurrents that result from the interaction of strong electric fields (tens of GV/m) with nanostructured materials [2][3][4][5][6][8][9][10]13,[15][16][17][19][20][21][22] (for review, see refs. 23,24 ).…”
mentioning
confidence: 99%
“…n recent years, the combination of nano-optical structures with intense, few-cycle laser sources has led to a new class of solid-state petahertz electronic devices with promising applications in time-domain metrology as well as information processing [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . These petahertz devices rely on the attosecond-level temporal response of optical-field-driven photocurrents that result from the interaction of strong electric fields (tens of GV/m) with nanostructured materials [2][3][4][5][6][8][9][10]13,[15][16][17][19][20][21][22] (for review, see refs. 23,24 ).…”
mentioning
confidence: 99%
“…While other direct time-domain optical sampling techniques for visible and near-infrared optical pulses currently exist 10,[12][13][14][15]17 , they require µJ-to mJ-level pulse energies, bulky apparatus, and/or vacuum enclosures. By providing a compact, chip-scale platform that enables sub-cycle, field-sensitive detection of subto few-fJ optical waveforms in ambient conditions, devices similar to those discussed in this work could find applications such as phase-resolved spectroscopy and imaging, and could have an impact in a variety of fields such as biology, medicine, food-safety, gas sensing, and drug discovery.…”
Section: Resultsmentioning
confidence: 99%
“…If readily available, sub-cycle optical-field sampling in the visible to near-infrared (near-IR) spectral regions would likewise provide great benefit to both science and industry. For example, attosecond streaking spectroscopy has been used to study the role of optical-field-controlled coherent electron dynamics in the control of chemical reaction pathways 7 and to investigate petahertz-level electrical currents in solid-state systems [8][9][10] . It was also recently shown that sub-cycle field sampling of the free-induction decays of biological systems can provide an order of magnitude reduction in the limits of detection and improved molecular sensitivity compared to traditional frequency-domain spectroscopic methods 11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several techniques enabling a full characterization of laser pulses have been developed since then. Like attosecond streaking, the majority of these field-sampling techniques rely on the use of a short auxiliary pulse providing a subcycle nonlinear gating [12][13][14][15][16][17]. In the time-domain observation of an electric field (TIPTOE) approach [13], a strong few-cycle phase-stable gating pulse tunnel ionizes a target gas, while the ionization rate is modulated by the much weaker field to be sampled.…”
Section: Introductionmentioning
confidence: 99%